HUBUNGAN ANTARA FAKTOR INTERNAL KELUARGA BURUH MIGRAN DENGAN PERTAMBAHAN ASSET RUMAH TANGGA - Lia Mutiara Setia; Rukmadi Warsito; Georgius Hartono (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2013)
The purpose of this study were to find out: push and pull factors of migrant workers working abroad, and the relationship between internal factors with increasing household assets. This research was conducted in the District Tuntang and Pabelan. Type of research is explanatory research, using two approaches namely quantitative and qualitative analysis approach. Sampling method using Step Cluster Sampling. The main data analyzed in this study were obtained from a study entitled “Indonesian Workers (TKI) Role and Influence People’s Economy In Rural Areas In Central Java Province (Seeking Pattern Development Investments) Year-2